2000
DOI: 10.1037/0278-7393.26.3.547
|View full text |Cite
|
Sign up to set email alerts
|

The source of feelings of familiarity: The discrepancy-attribution hypothesis.

Abstract: Many investigators have observed that the feeling of familiarity is associated with fluency of processing. The authors demonstrated a case in which the feeling of familiarity did not result from fluency per se; they argued that it resulted instead from perceiving a discrepancy between the actual and expected fluency of processing (B. W. A. Whittlesea & L. D. Williams, 1998). In this article, the authors extend that argument. They observed that stimuli that are experienced as strongly familiar when presented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
263
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(285 citation statements)
references
References 47 publications
18
263
0
4
Order By: Relevance
“…In recent years, the role of expectation and attribution in moderating the effects of fluency on judgments has been examined (Westerman, Lloyd, & Miller, 2002;Whittlesea & Williams, 1998, 2000, 2001. Whittlesea and Williams (1998), for example, demonstrated that enhanced perceptual fluency does not necessarily result in higher familiarity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the role of expectation and attribution in moderating the effects of fluency on judgments has been examined (Westerman, Lloyd, & Miller, 2002;Whittlesea & Williams, 1998, 2000, 2001. Whittlesea and Williams (1998), for example, demonstrated that enhanced perceptual fluency does not necessarily result in higher familiarity.…”
Section: Methodsmentioning
confidence: 99%
“…In Experiment 5, we added more orthographically regular nonwords to the stimuli in order to test the discrepancyattribution hypothesis (Whittlesea & Williams, 1998, 2000, 2001 for duration judgments. According to this hypothesis, perceptual fluency is attributed to the judgment at hand only if there is a discrepancy between expected fluency and actual fluency.…”
mentioning
confidence: 99%
“…One way fluency has been studied is with stimuli slowly emerging from noise (gradual unmasking), wherein the speed or fluency of item identification appears to be related to the tendency to report that the item had been seen previously (Verfaellie and Cermak 1999;Conroy et al 2005). Other methods have also been used to show that fluency can provoke "old" responses in recognition tests (e.g., Jacoby and Whitehouse 1989;Whittlesea and Williams 2000;Kleider and Goldinger 2004). Importantly, a bias to call fluently processed stimuli "old" can readily occur for stimuli not previously viewed (e.g., Verfaellie and Cermak 1999).…”
mentioning
confidence: 99%
“…In another fMRI study (Garoff, et al, 2005), encoding activity in the right fusiform gyrus (but not in the left fusiform) predicted memory for specific perceptual properties of stimuli. Thus, the right fusiform gyrus seems to be involved in processing item-specific perceptual information, which might underlie familiarity processes (Jacoby & Dallas, 1981;Whittlesea & Williams, 2000) (although see Voss & Paller, 2006). The role of the right fusiform gyrus in temporal-order decisions for longer lags might reflect greater reliance on perceptual aspects of the information during distance judgments.…”
Section: Regions Associated With Distance Processes During Longer Timmentioning
confidence: 99%